Central venous oxygen saturation as the predictor of the outcome from mechanical ventilation - Bhat, Imtiyaz Ahmad; Bashir, Farhana; Javed Iqbal Naqeshbandi; Malla, Mohmmad Sadiq (Asian Journal of Medical Sciences, 2022)
Background: Central venous oxygen saturation is being currently studied and used to guide extubation in patients on ventilator for more than 48 h. Aims and Objectives: The aim of our study was to compare chances of extubation failure after mechanical ventilation using conventional versus central venous oxygen saturation criteria for weaning from long-term mechanical ventilation. Materials and Methods: This prospective clinical study was conducted in the Postgraduate Department of Anaesthesiology and Critical Care, Government Medical College (GMC) Srinagar and was performed in the Surgical Intensive Care Unit at SMHS, an associated hospital of GMC Srinagar. In our study, fifty-two patients were studied out of which 25 patients were extubated by standard extubation criteria and 27 patients were extubated according to ScvO2 criteria and conventional criteria combined together. Results: Using conventional criteria on 25 patients from 52 patients, 56% had successful weaning while 44% had failure in weaning. Here, 11% should be 44%. While adding ScvO2 criteria on 27 of 52 patients, successful weaning was in 81.48% and failure in 18.52%. With sensitivity of 95.4%, specificity of 100%, positive predictive value of 100%, negative predictive value of 83.3%, and accuracy of 96.3% with confidence interval of 95%. Conclusion: ScvO2 criteria when added to conventional criteria help the clinician to estimate proper time for extubation and reduce the rates of reintubation.